2016
DOI: 10.1113/jp273024
|View full text |Cite
|
Sign up to set email alerts
|

Physiological roles of Kv2 channels in entorhinal cortex layer II stellate cells revealed by Guangxitoxin‐1E

Abstract: beyond -30 mV, but not transient, A-type current. In current clamp, GTx (1) had 9 virtually no effect on the first action potential, but markedly slowed repolarization of 10 late spikes during repetitive firing; (2) enhanced the after-depolarization (ADP); (3) 11 reduced fast and medium after-hyperpolarizations (fAHPs, mAHPs); (4) strongly 12 enhanced burst firing and increased excitability at moderate spike rates, but reduced 13 spiking at high rates; (5)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 69 publications
(214 reference statements)
3
17
0
Order By: Relevance
“…Liu and Bean (2014) observed modest spike broadening in CA1 pyramidal cells with GxTx. Honigsperger et al (2013) also observed that GxTx blocked I K but slowed AP repolarization only after the first AP during repetitive firing in ERC stellate cells (layer 2). Both CA1 pyramidal cells and ERC pyramidal cells typically have broader APs than neocortical pyramidal cells, which may allow for the relatively kinetically slow K v 2 channels to contribute to repolarization.…”
Section: Discussionmentioning
confidence: 81%
“…Liu and Bean (2014) observed modest spike broadening in CA1 pyramidal cells with GxTx. Honigsperger et al (2013) also observed that GxTx blocked I K but slowed AP repolarization only after the first AP during repetitive firing in ERC stellate cells (layer 2). Both CA1 pyramidal cells and ERC pyramidal cells typically have broader APs than neocortical pyramidal cells, which may allow for the relatively kinetically slow K v 2 channels to contribute to repolarization.…”
Section: Discussionmentioning
confidence: 81%
“…Based on this correlation, we would expect that decreasing K v 2.1 functional expression should increase AHP amp values. However, convergent genetic and pharmacological evidence suggests the opposite: decreasing K v 2.1 activity or expression decreases AHP amp values [ 45 , 46 ]. Delving deeper, the Kcnb1- AHP amp correlation appears driven in part by gross differences between excitatory and non-excitatory cell types, with excitatory cells strongly expressing Kcnb1 and also having small AHP amp relative to non-excitatory cell types ( S5C Fig ).…”
Section: Resultsmentioning
confidence: 99%
“…Based on this correlation, we would expect that decreasing K v 2.1 functional expression should increase AHP amp values. However, convergent genetic and pharmacological evidence suggests the opposite: decreasing K v 2.1 activity or expression decreases AHP amp values 42,43 . Delving deeper, the Kcnb1-AHP amp correlation appears driven in part by gross differences between excitatory and non-excitatory cell types, with excitatory cells strongly expressing Kcnb1 and also having small AHP amp relative to non-excitatory cell types (Supplemental Figure 4C).…”
Section: Causal Relationships Between Discovered Gene-electrophysiolomentioning
confidence: 99%